Mitochondrial telomerase protects cancer cells from nuclear DNA damage and apoptosis. - Chatchawan Singhapol; Deepali Pal; Rafal Czapiewski; Mahendar Porika; Glyn Nelson; Gabriele C Saretzki (PLoS ONE, 2013)
Most cancer cells express high levels of telomerase and proliferate indefinitely. In addition to its telomere maintenance function, telomerase also has a pro-survival function resulting in an increased resistance against DNA damage and decreased apoptosis induction. However, the molecular mechanisms for this protective function remain elusive and it is unclear whether it is connected to telomere maintenance or is rather a non-telomeric function of the telomerase protein, TERT. It was shown recently that the protein subunit of telomerase can shuttle from the nucleus to the mitochondria upon oxidative stress where it protects mitochondrial function and decreases intracellular oxidative stress. Here we show that endogenous telomerase (TERT protein) shuttles from the nucleus into mitochondria upon oxidative stress in cancer cells and analyzed the nuclear exclusion patterns of endogenous telomerase after treatment with hydrogen peroxide in different cell lines. Cell populations excluded TERT from the nucleus upon oxidative stress in a heterogeneous fashion. We found a significant correlation between nuclear localization of telomerase and high DNA damage, while cells which excluded telomerase from the nucleus displayed no or very low DNA damage. We modeled nuclear and mitochondrial telomerase using organelle specific localization vectors and confirmed that mitochondrial localization of telomerase protects the nucleus from inflicted DNA damage and apoptosis while, in contrast, nuclear localization of telomerase correlated with higher amounts of DNA damage and apoptosis. It is known that nuclear DNA damage can be caused by mitochondrially generated reactive oxygen species (ROS). We demonstrate here that mitochondrial localization of telomerase specifically prevents nuclear DNA damage by decreasing levels of mitochondrial ROS. We suggest that this decrease of oxidative stress might be a possible cause for high stress resistance of cancer cells and could be especially important for cancer stem cells.